2022
DOI: 10.1158/1538-7445.am2022-5519
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 5519: Selinexor synergizes with anti-PD-1 antibody and inhibits tumor growth and metastasis in syngeneic mouse models of KRAS mutant colorectal cancer

Abstract: Background: Colorectal cancer (CRC) is the second leading cause of cancer related death. In approximately half of all CRC cases, oncogenic KRAS mutations underlie poor prognosis and drug resistance. A previous multi-genomic analysis of 4,725 biological processes with 106 human non-small-cell lung cancer cells identified nuclear transport machinery as the sole process selectively required for the survival of KRAS mutant cells. Selinexor is a clinically approved oral inhibitor of nuclear export protein Exportin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…17 Preclinical studies reported an increased antitumor activity in animal models, when a combination of selinexor and anti-PD-1 antibody administered concurrently compared with the monotherapy by altering the local immune environment, notably by increasing the relative number of T cells and NKT cells with a concomitant reduction in Gr1+ and CD11b+ myeloid cells and Foxp3+ regulatory T cells. 18,19 Selinexor has been investigated in hematologic and solid malignancies as monotherapy and in combination with chemotherapy in different therapy doses. The U.S. Food and Drug Administration approved selinexor for the treatment of previously treated relapsed or refractory diffuse large B-cell lymphoma and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Preclinical studies reported an increased antitumor activity in animal models, when a combination of selinexor and anti-PD-1 antibody administered concurrently compared with the monotherapy by altering the local immune environment, notably by increasing the relative number of T cells and NKT cells with a concomitant reduction in Gr1+ and CD11b+ myeloid cells and Foxp3+ regulatory T cells. 18,19 Selinexor has been investigated in hematologic and solid malignancies as monotherapy and in combination with chemotherapy in different therapy doses. The U.S. Food and Drug Administration approved selinexor for the treatment of previously treated relapsed or refractory diffuse large B-cell lymphoma and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenic activities of selinexor had been described in preclinical models, where it increased PDCD1 and CTLA4 gene expression in leukocytes and induced CD274 gene expression in human melanoma cell lines 17 . Preclinical studies reported an increased antitumor activity in animal models, when a combination of selinexor and anti–PD‐1 antibody administered concurrently compared with the monotherapy by altering the local immune environment, notably by increasing the relative number of T cells and NKT cells with a concomitant reduction in Gr1+ and CD11b+ myeloid cells and Foxp3+ regulatory T cells 18,19 …”
Section: Introductionmentioning
confidence: 99%